Energy dispersive X-ray microanalysis of elemental distribution in raw and germinated brown rice varieties - Ismail, Maznah; Abdul Hadi, Nordiana; Haroun, Rafiuz Zaman; Musa, Siti Nor Asma; Imam, Mustapha Umar (Taylor & Francis, 2014)
In this study, the mineral composition of germinated brown rice, brown rice, and white rice was evaluated. Brown rice grain was processed through a combination of chemical pretreatment and low oxygen treatment, after which germination was confirmed through imaging under a microscope. Using energy dispersive X-ray analysis, Mg, Al, and Cl were found to be slightly higher in germinated brown rice than in brown rice and white rice. These variations in the mineral content of germinated brown rice were attributed to the joint effect of the germination process and the prior soaking. The inability of energy dispersive X-ray to detect other minerals suggested that it was not sensitive and, hence, it was not suitable for studying elemental distribution in rice grains, or maybe the elements were not present in the rice grains studied.